Beetle Conservation - New, T. R.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
Interest in beetle conservation has long been evident, with many papers treating these abundant, ecologically important and popular insects. However, this issue of Journal of Insect Conservation is the first to be dedicated entirely to beetles, and contains a number of papers, predominantly from outside western Europe, to demonstrate the variety and scope of problems and conservation concerns that surround these insects. A short introductory perspective is followed by eight original contributions, in which beetles from many parts of the world are considered, and in which some major threats to their wellbeing are evaluated. Reprinted from Journal of Insect Conservation, Volume 11, No. 1, 2007
Beetles and conservation -- The effects of forestry on carabid beetles (Coleoptera: Carabidae) in boreal forests -- Conservation status of Prodontria (Coleoptera: Scarabaeidae) species in New Zealand -- Conservation status of Prodontria (Coleoptera: Scarabaeidae) species in New Zealand -- Carabid beetle (Coleoptera: Carabidae) conservation in New Zealand -- Notes on the habitat and adult behaviour of three red-listed Colophon spp. (Coleoptera: Lucanidae) of the Cape Floristic Region, South Africa -- Are we doomed to repeat history? A model of the past using tiger beetles (Coleoptera: Cicindelidae) and conservation biology to anticipate the future -- Unfortunate encounters? Novel interactions of native Mecyclothorax, alien Trechus obtusus (Coleoptera: Carabidae), and Argentine ant (Linepithema humile, Hymenoptera: Formicidae) across a Hawaiian landscape -- Water beetles associated with reservoirs on Table Mountain, Cape Town: implications for conservation -- The decline of native coccinellids (Coleoptera: Coccinellidae) in the United States and Canada.
Keywords: LIFE SCIENCES; BIODIVERSITY; ENTOMOLOGY; LIFE SCIENCES; ENTOMOLOGY; BIODIVERSITY